Disney's The jungle book 2. - Disney Enterprises (1996- ) (New York : Scholastic, 2003)
Romp through the jungle with Mowgli and friends in this Disney classic; part of Disney's Wonderful World of Reading program.
Keywords: Kipling, Rudyard, -- 1865-1936. -- Adaptations; Mowgli -- (Fictitious character) -- Pictorial works -- Juvenile fiction